Exploring the Impact of Lifestyle Habits and Environmental Factors on the Risk of Hypertension in Rural Populations - Apriza Apriza; Zainab Mohd Shafie; Prapaporn Langputeh; Muhammad Nurman (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Hypertension remains a significant risk factor for cardiovascular disease (CVD), stroke, and kidney failure, particularly in low- and middle-income countries (LMICs), where access to healthcare is often limited. This study explores the impact of lifestyle habits and environmental factors on the risk of hypertension in rural ethnic minority populations.Method: A cross-sectional study was conducted with 1,500 participants from the rural area of Tarai Bangun village in Kampar Regency, Riau Province, Indonesia, focusing on lifestyle habits such as eating habits, physical activity, smoking, alcohol consumption, and environmental conditions like air quality, pedestrian convenience, and access to health. This study used stratified random sampling, bivariate test analysis, and multivariate logistic regression analysis. This study aimed to determine the impact of lifestyle habits and environmental factors on hypertension in rural communities.Result: The prevalence of hypertension in this population was 45.6%, with rural areas having a higher incidence of systolic-diastolic hypertension (SDH) than urban populations, who had a higher prevalence of isolated systolic hypertension (ISH). Major lifestyle factors such as smoking (39.7%), alcohol consumption (45.6%), and high sodium intake, all had a substantial association with hypertension in both urban and rural settings. Environmental factors such as poor pedestrian convenience and limited access to healthcare were found to contribute to a higher prevalence of hypertension among rural populations. In contrast, better air quality and access to green space were associated with lower rates of hypertension in urban settings. Socio-economic factors, especially lower income and education levels, are also associated with an increased risk of hypertension. The study highlights the importance of tailored public health interventions in rural ethnic minority populations, with a focus on reducing risky behaviors such as smoking and alcohol consumption, improving eating habits, and increasing access to health care. In addition, urban and environmental planning policies that encourage physical activity and improve air quality can considerably lower the risk of hypertension in urban populations. These findings underscore the importance of addressing lifestyle and environmental factors when managing hypertension in underserved rural communities.